2020
DOI: 10.26434/chemrxiv.12055218.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suzuki–Miyaura cross-coupling for chemoproteomic applications

Abstract: Bioorthogonal chemistry is a mainstay of chemoproteomic sample preparation workflows. While numerous transformations are now available, chemoproteomic studies still rely overwhelmingly on copper-catalyzed azide –alkyne cycloaddition (CuAAC) or 'click' chemistry. Here we demonstrate that gel-based activity-based protein profiling (ABPP) and mass-spectrometry-based chemoproteomic profiling can be conducted using Suzuki–Miyaura cross-coupling. We identify reaction conditions that proceed in complex cell lysates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…As observed both in our prior study [27] and here, sample decontamination for chemoproteomic applications that rely on increased concentration of biotin capture reagents (e.g biotinazide and related molecules) is an essential step to achieve high coverage of biotinylated peptides. When benchmarked against standard CHCl3/MeOH protein precipitation, we found that the SP3 method, which relies on carboxyl coated magnetic beads, yields better coverage of biotin-labelled peptides.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…As observed both in our prior study [27] and here, sample decontamination for chemoproteomic applications that rely on increased concentration of biotin capture reagents (e.g biotinazide and related molecules) is an essential step to achieve high coverage of biotinylated peptides. When benchmarked against standard CHCl3/MeOH protein precipitation, we found that the SP3 method, which relies on carboxyl coated magnetic beads, yields better coverage of biotin-labelled peptides.…”
Section: Discussionsupporting
confidence: 64%
“…Our recent study revealed that solid phase-enhanced samplepreparation (SP3), a method that uses carboxyl coated magnetic beads to separate proteins and peptides from contaminates, can increase the recovery of biotinylated peptides when lower concentrations of IAA and biotin-azide were used for labeling (200 µM and 400 µM, respectively). [27] Therefore, we sought to determine whether this improved recovery would extend to samples treated with our optimized labeling conditions (2 mM IAA and 4 mM biotin-azide). Our first step was to optimize two key parameters for SP3 cleanup, (1) the ratio of protein material to magnetic beads and (2) elution conditions to maximize recovery of peptides after cleanup.…”
Section: Solid Phase-enhanced Sample-preparation (Sp3) For Cysteine Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 1 and 3 were prepared as has been reported [27] and synthesis of compound 4 was performed according to the previous studies [12] .…”
Section: Synthesis Of Reagentsmentioning
confidence: 99%